Wide Application of Minimally Processed Saliva on Multiple RT-qPCR Kits for SARS-CoV-2 Detection in Indonesia - Mahendra, Caroline; Kaisar, Maria Mardalena Martini; Vasandani, Suraj Rajan; Surja, Sem Samuel; Tjoa, Enty; Chriestya, Febie; Junusmin, Kathleen Irena; Widowati, Tria Asri; Irwanto, Astrid; Ali, Soegianto (Frontiers in Cellular and Infection Microbiology, 2021)
Saliva as a sample matrix has been an attractive alternative for the detection of SARS-CoV-2. However, due to potential variability in collection and processing steps, evaluating a proposed workflow amongst the local population is recommended. Here, we aim to validate the collection and treatment of human saliva as a direct specimen for RT-qPCR-based detection of SARS-CoV-2 in Indonesia. We demonstrated that SARS-CoV-2 target genes were detected in saliva specimens and remained stable for five days refrigerated or room temperature storage. The method of processing saliva specimens described in this report bypasses the need for an RNA-extraction process, thereby reducing the cost, time, and manpower required for processing samples. The developed method was tested across nine commercial kits, including the benchmark, to demonstrate its wide applicability on multiple existing workflows. Our developed method achieved 86% overall agreement rate compared to paired nasopharyngeal and oropharyngeal swab specimens (NPOP). With the assistance of a saliva sampling device, the collection was found to be more convenient for individuals and improved the overall agreement rate to 97%.